Genome sequencing of oomycete isolates from Chile supports the New Zealand origin of Phytophthora kernoviae and makes available the first Nothophytophthora sp. genome. (5th December 2018) - Studholme, David J.; Panda, Preeti; Sanfuentes Von Stowasser, Eugenio; González, Mariela; Hill, Rowena; Sambles, Christine; Grant, Murray; Williams, Nari M.; McDougal, Rebecca L.
Summary: Genome sequences were generated for six oomycete isolates collected from forests in Valdivia, Chile. Three of the isolates were identified morphologically as Phytophthora kernoviae, whereas two were similar to other clade 10 Phytophthora species. One isolate was tentatively identified as Nothophytophthora valdiviana based on nucleotide sequence similarity in the cytochrome oxidase 1 gene. This is the first genome sequence for this recently described genus. The genome assembly was more fragmented and contained many duplicated genes when compared with the other Phytophthora sequences. Comparative analyses were performed with genomic sequences of the P. kernoviae isolates from the UK and New Zealand. Although the potential New Zealand origin of P. kernoviae has been suggested, new isolations from Chile had cast doubt on this hypothesis. We present evidence supporting P. kernoviae as having originated in New Zealand. However, investigation of the diversity of oomycete species in Chile has been limited and warrants further exploration. We demonstrate the expediency of genomic analyses in determining phylogenetic relationships between isolates within new and often scantly represented taxonomic groups, such as Phytophthora clade 10 and Nothophytophthora . Data are available on GenBank via BioProject accession number PRJNA352331.